56Fe, 16O, 1H Elastic and capture cross sections analysis in PCA-REPLICA benchmark. (December 2021) - Kaddour, M.; El Bardouni, T.; Boukhal, H.; Makhloul, M.; Chakir, E.
Abstract: The uncertainties in nuclear data give inaccurate values of reaction rates in shielding benchmarks. Consequently, the inclusion of the shielding benchmarks in the validation of the nuclear data would contribute to the production of general-purpose nuclear data evaluations. The validation of nuclear data goes through an essential step of sensitivity and uncertainty analysis. During this step, the evaluator determines which nuclear data necessitate adjustment. In this work, sensitivity and uncertainty analysis of reaction rates due to two primordial cross sections elastic and capture uncertainties of important isotopes in PCA-REPLICA benchmark are carried out. The reaction rates and their sensitivities are calculated by MCNP6.1 code. The weight window and energy cut-offs are two variance reduction techniques used in this calculation. The covariance matrices of the studied cross sections are processed by NJOY99 software. The sensitivities and uncertainties of the estimated reaction rates are calculated in four energy groups for three detectors 103 Rh (n, n') 103 Rh m, 115 In (n, n') 115 In m and 32 S (n, p) 32 P. The obtained results show that the elastic cross sections of 56 Fe, 16 O and 1 H give large uncertainties on reaction rates, whereas the captures of these isotopes have small uncertainties on reaction rates. The analysis of the sensitivities and the uncertainties of the reaction rates due to elastic and capture cross sections of the 56 Fe, 1 H and 16 O indicate that the elastic cross section of 56 Fe needs improvement in the energy range 0.1 MeV–19.60 MeV and the elastic cross sections of 1 H and 16 O need adjustments in the energy range 1.35 MeV–19.60 MeV. Highlights: Reaction rates calculation in PCA-REPLICA using variance reduction techniques. 56 Fe, 1 H, 16 O cross sections analysis using Rh-103 (n, n')Rh-103m detector. 56 Fe, 1 H, 16 O cross sections analysis using In-115 (n, n')In-115m detector. 56 Fe, 1 H, 16 O cross sections analysis using S-32 (n, p)P-32 detector.